Maturation and culture affect the metabolomic profile of oocytes and follicular cells in young and old mares - Bresnahan, D. R.; Catandi, G. D.; Peters, S. O.; Maclellan, L. J.; Broeckling, C. D.; Carnevale, E. M. (Frontiers in Cell and Developmental Biology, 2024)
Oocytes and follicular somatic cells within the ovarian follicle are altered during maturation and after exposure to culture in vitro. In the present study, we used a nontargeted metabolomics approach to assess changes in oocytes, cumulus cells, and granulosa cells from dominant, follicular-phase follicles in young and old mares. Samples were analyzed at three stages associated with oocyte maturation: (1) GV, germinal vesicle stage, prior to the induction of follicle/oocyte maturation in vivo; (2) MI, metaphase I, maturing, collected 24 hours after induction of maturation in vivo; and (3) MIIC, metaphase II, mature with collection 24 hours after induction of maturation in vivo plus 18 hours of culture in vitro. Samples were only analyzed when all three stages of a cell type were obtained from the same mare. Significant differences in metabolite abundance were most often associated with MIIC, with some of the differences appearing to be linked to the final stage of maturation and others to exposure to culture medium. While differences occurred for many metabolite groups, some of the most notable were detected for energy and lipid metabolism and amino acid abundance. The study demonstrated that metabolomics has potential to aid in optimizing culture methods and evaluating cell culture additives to support differences in COCs associated with maternal factors.